AG-NGS: A powerful and user-friendly computing application for the semi-automated preparation of next-generation sequencing libraries using open liquid handling platforms - Sergio Callejas; Rebeca Álvarez; Alberto Benguria; Ana Dopazo (BioTechniques)
Next-generation sequencing (NGS) is becoming one of the most widely used technologies in the field of genomics. Library preparation is one of the most critical, hands-on, and time-consuming steps in the NGS workflow. Each library must be prepared in an independent well, increasing the number of hours required for a sequencing run and the risk of human-introduced error. Automation of library preparation is the best option to avoid these problems. With this in mind, we have developed automatic genomics NGS (AG-NGS), a computing application that allows an open liquid handling platform to be transformed into a library preparation station without losing the potential of an open platform. Implementation of AG-NGS does not require programming experience, and the application has also been designed to minimize implementation costs. Automated library preparation with AG-NGS generated high-quality libraries from different samples, demonstrating its efficiency, and all quality control parameters fell within the range of optimal values.